Straightforward Probing of Polarization and Spin-Resolved Transmission through Potential Barriers in Silicene - Diana Meneses-Gustin; Marcos R. S. Tavares (Advances in Condensed Matter Physics)
The low-energy physics of silicene is described by Dirac electrons with a strong spin-orbit interaction and its band structure can be controlled by an external electric field Ez. We evaluate the electronic transmission through single and double barriers in silicene as a function of the angle of incidence θ, the electron energy E, and the strength of the field Ez. We find a spin-resolved transmission, reflected in the polarization P, and a conductance qualitatively different in some ranges of E than that in graphene. P exhibits quasiperiodic resonances versus θ in double-barrier structures.